Evaluation of analgesic protocol effect on calf behavior after concurrent castration and dehorning - Pauly, C.; White, Bradley J.; Coetzee, J. F.; Robért, B.; Baldridge, S.; Renter, David G. (My University, 2012)
Castration and dehorning are common procedures in the US cattle industry, but the impact of analgesic programs on post-surgical behavior is not well documented. The research objective was to determine the impact of three different analgesic protocols: (sodium salicylate; a combination of xylazine, ketamine and butorphanol; and both treatments together) compared to the absence of analgesia on cattle behavior after concurrent castration and dehorning. Accelerometers recorded activity on 40 calves for three periods of time: prior to sham surgery, between sham and actual surgery, and 4 days post-surgery. Significant interactions (P<0.05) were found between treatment and time relative to surgery. Cattle treated with a combination of ketamine, butorphanol, and sodium salicylate spent more time lying after the procedures compared to cattle receiving only xylazine, ketamine, and butorphanol.
Keywords: Analgesic protocols; Calves; Dehorning; Castration